2016
DOI: 10.1111/pce.12703
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes in leaf water of terrestrial plants

Abstract: Leaf water contains naturally occurring stable isotopes of oxygen and hydrogen in abundances that vary spatially and temporally. When sufficiently understood, these can be harnessed for a wide range of applications. Here, we review the current state of knowledge of stable isotope enrichment of leaf water, and its relevance for isotopic signals incorporated into plant organic matter and atmospheric gases. Models describing evaporative enrichment of leaf water have become increasingly complex over time, reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
431
4
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(464 citation statements)
references
References 140 publications
(243 reference statements)
27
431
4
2
Order By: Relevance
“…This absence of a relationship between 17 O-excess and tree cover density is also mirrored in Fig. 4 Cernusak et al, 2016;Landais et al, 2006;Li et al, 2017). The average value of λ LW−IW (0.519) is close to the value of θ diff calculated for the diffusion of vapor in air (0.518; Barkan and Luz, 2007).…”
Section: Irrigation and Soil Watersmentioning
confidence: 62%
See 3 more Smart Citations
“…This absence of a relationship between 17 O-excess and tree cover density is also mirrored in Fig. 4 Cernusak et al, 2016;Landais et al, 2006;Li et al, 2017). The average value of λ LW−IW (0.519) is close to the value of θ diff calculated for the diffusion of vapor in air (0.518; Barkan and Luz, 2007).…”
Section: Irrigation and Soil Watersmentioning
confidence: 62%
“…It has been shown that the δ 18 O Phyto of grass stems weakly affected by transpiration correlated with the δ 18 O signature of soil water (δ 18 O SW ) and the atmospheric temperature, as expected for a polymerization of silica in isotope equilibrium with the plant water (Webb and Longstaffe, 2000. It has also been shown that δ 18 O Phyto from grass leaves correlated with RH, as expected for an evaporative kinetic isotope enrichment of the leaf water (e.g., Cernusak et al, 2016) imprinted on δ 18 O Phyto . However, because grass stem and leaf phytoliths have the same morphology and are mixed in soil and sedimentary samples, these calibrations were not sufficient for using δ 18 O Phyto of grassland phytolith assemblages as a paleoclimatic signal.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…This opens the door for large-scale assessment of the soil-vegetation-atmosphere interactions in the water cycle. In particular, these developments have enhanced the spatial and temporal resolution tremendously, furthering the understanding in the fields of plant ecophysiology (Cernusak et al, 2016) and ecosystem physiology (Dubbert et al, 2014a, c).…”
mentioning
confidence: 99%